2012
DOI: 10.5090/kjtcs.2012.45.6.408
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculous Aortitis Complicated with Pseudoaneurysm Formation in the Descending Thoracic Aorta: A Case Report

Abstract: A 51-year-old male with sustained fever was diagnosed with military tuberculosis and tuberculous aortitis complicated with pseudoaneurysm formation at the proximal descending aorta. A follow-up computed tomography evaluation showed an increased size of the pseudoaneurysm in this area, suggestive of a contained rupture. Consequently, the patient underwent emergency excision and replacement of the aorta using a left heart bypass. The patient was discharged without postoperative complications on post-operative da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…A review of the English literature from 2008 to today revealed 28 more cases (Table 1) [3], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], specifically 18 men and 10 women with a mean age of 44.64 ± 18.16 years (range 16–84). 7 patients had a history of pulmonary tuberculosis and had previously received anti-tuberculosis medication.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the English literature from 2008 to today revealed 28 more cases (Table 1) [3], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], specifically 18 men and 10 women with a mean age of 44.64 ± 18.16 years (range 16–84). 7 patients had a history of pulmonary tuberculosis and had previously received anti-tuberculosis medication.…”
Section: Discussionmentioning
confidence: 99%
“…Lung window revealed multiple centrilobular and "tree-in-bud' nodules along with minimal pericar- Based on clinical and imaging features the possibility of tuberculous aortitis was considered. Tuberculous aortitis is extremely rare and is usually secondary to local infiltration (mediastinal lymph adenopathy or vertebral cold abscess) or haematogenous spread (unlikely) [10]. Pseudoaneurysm develops secondary to infective aortitis causing weakening of the aortic wall.…”
Section: Tuberculous Aortitismentioning
confidence: 99%
“…Tuberculous aortitis occurs in less than 1% of patients with latent tuberculosis, but mortality rates are as high as 60%. The high mortality associated with this disease is related to the perforation of the pseudoaneurysm into the adjacent organs, causing fatal extravasation [6,8]. Tuberculous aortic aneurysm can develop despite anti-tuberculous medication, probably due to poor drug penetration into caseous necrotic tissue.…”
Section: Tuberculous Aortitismentioning
confidence: 99%
“…Tuberculous aortic aneurysm can develop despite anti-tuberculous medication, probably due to poor drug penetration into caseous necrotic tissue. Therefore, combination medical and surgical approaches are required for successful management [8,9].…”
Section: Tuberculous Aortitismentioning
confidence: 99%